2009
DOI: 10.1292/jvms.001617
|View full text |Cite
|
Sign up to set email alerts
|

The Feeding Behavior of Dogs Correlates with their Responses to Commands

Abstract: ABSTRACT. Motivation is one of the most important factors in dog training. To generate motivation, people use various reinforcer mechanisms. In particular, many pet owners use food because it is simple and convenient. The aim of this study was to investigate the association between dogs' level of interest in food and their responsiveness to commands. Thirty-four dogs were divided into three groups based on their feeding patterns (Fast, Slow, and Leftover). The fast group (n=15) had the highest interest in food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…It appears that the satiety centers in these dogs are not functioning. They experience difficulty during training when switching from food to a secondary reinforcement, and thus they sometimes reject the owner’s commands when a food reward is not used [ 19 ]. While food is a convenient reinforcement tool, it is difficult to build good owner–dog relationship if the owners do not understand their dog’s levels of interest in food [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that the satiety centers in these dogs are not functioning. They experience difficulty during training when switching from food to a secondary reinforcement, and thus they sometimes reject the owner’s commands when a food reward is not used [ 19 ]. While food is a convenient reinforcement tool, it is difficult to build good owner–dog relationship if the owners do not understand their dog’s levels of interest in food [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They experience difficulty during training when switching from food to a secondary reinforcement, and thus they sometimes reject the owner’s commands when a food reward is not used [ 19 ]. While food is a convenient reinforcement tool, it is difficult to build good owner–dog relationship if the owners do not understand their dog’s levels of interest in food [ 19 ]. Okamoto et al [ 19 ] also demonstrated that the feeding speed (g/sec) and the amount of food consumed per mouthful did not depend on sex, age, or the dogs’ body size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying effective reinforcers is essential for training and maintaining desirable behaviors across species. In domestic dogs, prior research has identified food as an effective positive reinforcer (Feuerbacher & Wynne, 2012; Fukuzawa & Hayashi, 2013; Okamoto et al, 2009). Despite its utility as a reinforcer, using food requires extra effort on the part of the owner, as it must be prepared and carried during training.…”
mentioning
confidence: 99%
“…Research investigating the use of food as an effective reinforcer for dog behavior has found that food typically resulted in more correct responses to human obedience cues than petting or praise (Okamoto et al, 2009). Similarly, Fukuzawa and Hayashi (2013) found that, in comparison to petting or praise, food reinforcement resulted in dogs reaching criterion faster for the behaviors of sit, stay, and come, and resulted in faster responding during recall (come).…”
mentioning
confidence: 99%